Claiming the future of enterprise education. Issue 8 (4th November 2014) - Jones, Colin; Matlay, Harry; Penaluna, Kathryn; Penaluna, Andy
Abstract : Purpose: – The purpose of this paper is to highlight the importance of enterprise educators working collectively to develop a unique scholarship of teaching. The authors argue that the time is right for educators in this domain to secure the future of enterprise education. Acknowledging the debate between "entrepreneurship education" and "enterprise education, " the authors set out to develop a unification model through which educators can act collectively to demonstrate the leadership required to secure the autonomy of the domain. Design/methodology/approach: – The authors bring several pertinent ideas (pedagogical content knowledge, heutagogy and academagogy) to the attention of academics/researchers involved in the design, development and delivery of enterprise education. The innovative approach to combine these ideas with prevailing thinking in this domain has facilitated a model for collective action. Findings: – It is at the level of the shared philosophical positions that the authors can best cooperate to shape the future direction of enterprise education. The authors argue against dwelling upon how the authors differ in terms of context and process issues. Such matters can only fragment the theory and practice of enterprise education. The authors need to develop greater appreciation of shared philosophical positions and leverage this understanding into a unique scholarship of teaching, specific to enterprise education. Practical implications: – As enterprise education becomes more global, it is also likely to become more attractive to business schools that long for a new positioning tool in the increasingly overcrowded markets that they compete in. Originality/value: – This paper encourages enterprise educators to reflect upon the knowledge they hold of their own practice, and that of other enterprise educators.